MORPHOLOGICAL INDICES: DISTINGUISHING SINGLE AND TRIPLETS-BEARING BOER AND ETAWA GRADE GOATS IN LOMBOK BARAT - Fitriyah, Abyadul; Mariani, Yuni; Kartika, Ni Made Andry; Fajri, Nefi Andriana; Alimuddin; Harmayani, Ria (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2024)
This study aimed to identify female goats with the potential to give birth to triplets by examining morphological characteristics correlated with FSH and LH hormone levels in the blood. It included four triplet-bearing Boer goats and four triplet-bearing Etawah grade goats, each with 12 kids, and four single-bearing Boer goats and four single-bearing Etawah grade goats, each with four kids. Morphological indices of body sizes, including weight, height slope, length index, width slope, depth index, foreleg length, and hormone levels, were observed. A t-test and descriptive analysis were conducted. The average body size of Boer goats was larger than Etawah grade goats, but there were no significant morphological differences between triplet-bearing Boer and Etawah grade goats. However, single-bearing Boer goats had a significantly higher height slope than single-bearing Etawah grade goats. FSH levels significantly increased in the blood of triplet-bearing Boer goats compared to single-bearing Boer goats. Morphological indices and hormone levels can help select goats likely to give birth to triplets.